RE – LAYOUT GUDANG PRODUK JADI SAK SEMEN DENGAN MENGGUNAKAN METODE SHARE STORAGE AREA PACKER TUBAN IV PADA PT. SEMEN INDONESIA (PERSERO) TBK - Dwi Nur Aliyah Firdasafitri; Zainal Arief (LPPM Universitas Bina Bangsa, 2023)
Warehouse of raw materials at PT. Semen Indonesia (Persero) Tbk in the Tuban IV Packer Area has an irregular arrangement, causing errors in picking up goods and damage to cement bags. Therefore, designing a warehouse layout using the share storage (FIFO) method. The share storage method will prioritize the use of the nearest storage area according to the FIFO principle, while the database will help monitor and control warehouse inventory. The design results show that a storage area of ​​65 areas is required with a total area of ​​443.625 m2. The method used for warehouse management is the shared storage method, which regulates the placement of raw materials according to the FIFO (First In First Out) principle. This helps minimize bag damage and ensures efficient use of space. The result of this research is an optimal warehouse layout design using the shared storage method. With the implementation of this design, it is expected that PT. Semen Indonesia (Persero) Tbk can increase the efficiency and effectiveness of warehouse operations and reduce company losses due to damage to inefficient cement bags